Bring Up the Exhibits: GIS and the Humanities at Cornell University Library - Michev, Boris (Qualitative and Quantitative Methods in Libraries; Vol 2 No 3 (2013): September 2013 Issue, 2017)
The paper describes the efforts of the Cornell University Library and the Maps Unit in particular to reach out to audiences that are notusually identified as our “primary audience.” For decades there have been no geography departments in most of the top private universities in the United States, including Cornell. Thus, the University Library’s Map Collection is in the unique and somewhat awkward position of not having a “primary audience.”  In its absence we try to provide support to a broader audience primarily in the humanities. The paper brings together the various outreach and teaching initiatives of the Map Collection and argues that the absence of a “home” department is not an impediment to the research and learning potential of maps special collections and GIS technologies.